COMPARATIVE GENOMICS AND THE EVOLUTION OF PATHOGENICITY IN HUMAN PATHOGENIC FUNGI - MORAN, GARY; SULLIVAN, DEREK; COLEMAN, DAVID (My University, 2011)
Because most fungi have evolved to be free-living in the environment and because the infections they cause are usually opportunistic in nature, it is often difficult to identify specific traits that contribute to fungal pathogenesis. In recent years, there has been a surge in the number of sequenced genomes of human fungal pathogens, and comparison of these sequences has proved to be an excellent resource for exploring commonalities and differences in how these species interact with their hosts. In order to survive in the human body, fungi must be able to adapt to new nutrient sources and environmental stresses. Therefore, genes involved in carbohydrate and amino acid metabolism and transport and genes encoding secondary metabolites tend to be overrepresented in pathogenic species (e.g., Aspergillus fumigatus). However, it is clear that human commensal yeast species such as Candida albicans have also evolved a range of specific factors that facilitate direct interaction with host tissues. The evolution of virulence across the human pathogenic fungi has occurred largely through very similar mechanisms. One of the most important mechanisms is gene duplication and the expansion of gene families, particularly in subtelomeric regions. Unlike the case for prokaryotic pathogens, horizontal transfer of genes between species and other genera does not seem to have played a significant role in the evolution of fungal virulence. New sequencing technologies promise the prospect of even greater numbers of genome sequences, facilitating the sequencing of multiple genomes and transcriptomes within individual species, and will undoubtedly contribute to a deeper insight into fungal pathogenesis.
PUBLISHED
Keywords: Genome sequencing; comparative genomics; fungi; pathogenesis; evolution; Genes & Society; Immunology, Inflammation & Infection